2013
DOI: 10.1007/s11883-013-0358-0
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency and Cardiovascular Disease: An Updated Review of the Evidence

Abstract: Body iron status has been suggested to be related to the development of cardiovascular disease (CVD). Biologically plausible mechanisms for this association have been described, however epidemiological studies on iron status and CVD risk have provided conflicting results. The lack of consistency is likely explained by differences in the study design, the measures used for the assessment of iron status, the definition of outcomes, and adjustment for confounders. To help clarify the available evidence, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 86 publications
1
53
1
Order By: Relevance
“…Body iron stores (ferritin) have been associated with increased risk of CVD [34], [35] while depletion may be a cardioprotective mechanism [36], [37]. But this is highly controversial because iron deficiency too has been associated with increased cardiovascular risk [38].…”
Section: Discussionmentioning
confidence: 99%
“…Body iron stores (ferritin) have been associated with increased risk of CVD [34], [35] while depletion may be a cardioprotective mechanism [36], [37]. But this is highly controversial because iron deficiency too has been associated with increased cardiovascular risk [38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that both elevated and decreased markers of iron status enhance the risk for CV disease . However, conflicting results have also been reported . Furthermore, studies in haemodialysis patients or women from the general population have suggested a role for elevated hepcidin levels in the pathogenesis of atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…Biologically plausible mechanisms for this association have been described, however, epidemiological studies on iron status and CVD risk have provided conflicting result (9). Extreme conditions of iron deficiency, as well as of iron overload, are associated with modestly increased CVD risk, although with different proposed mechanisms (9). The findings support the concept that arterial plaque iron is a modifiable risk factor for atherogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies show that iron may play a key role in plaque vulnerability and contributes to plaque hemorrhage (13,14). Biologically plausible mechanisms for this association have been described, however, epidemiological studies on iron status and CVD risk have provided conflicting result (9). Extreme conditions of iron deficiency, as well as of iron overload, are associated with modestly increased CVD risk, although with different proposed mechanisms (9).…”
Section: Discussionmentioning
confidence: 99%